Medicinal uses of Cannabis sp. - Souza, Amanda Aparecida Fernandes de (2021)
The therapeutic properties of Cannabis have been described since antiquity and are of great relevance for the Egyptian, Chinese, Indian, Arab and Latin people. Cannabis-based medicines show several therapeutic purposes, mainly to treat disorders as constipation, some types of pain, epilepsy, anxiety and among others. In addition, the genus Cannabis exhibits great clinical relevance due to its Central Nervous System activities attributed to some phytochemicals compounds, as cannabidiol and Δ9-tetrahydrocannabinol. The interest in the pharmacological properties of Cannabis is growing and several new studies are being carried out to prove its pharmacotherapeutic use which are important to design of novel drugs with different routes of administration and for multiple pathologies resistant to the conventional treatments. In this context, there is a pressure on countries to review the laws that still limit the research development related to medicinal Cannabis purposes. Herein, our aim is to perform an overview about the plant, endocannabinoid system, Cannabis-based medicines and clinical uses, regulatory aspects of Cannabis sp and its chemical compounds of therapeutic interest.